Fatal transfusion reaction due to Serratia marcescens. Issue 6 (November 1967) - Black, W. A.; Pollock, A.; Batchelor, Elizabeth L.
Abstract : A fatal blood transfusion reaction due to contamination of the blood by Serratia marcescens is described. The diagnosis and treatment of such cases is described briefly. The importance of teamwork in all concerned with blood transfusion is stressed.